Examining the factor structure and validity of the WHOQOL-AGE among the oldest-old Chinese in Singapore - Cheng, Grand H.-L.; Feng, QiuShi; Chong, Yap-Seng; Koh, Woon-Puay (Frontiers in Public Health, 2023)
Objectives A short measure of quality of life in old age is essential. The present study examined the factor structure and validity of the 13-item WHOQOL-AGE among the oldest-old. Methods Data came from 1,000 Chinese aged ≥85 years in Singapore. Exploratory and confirmatory factor analyzes were conducted on the WHOQOL-AGE. Regression examined the demographic, social and health correlates of the identified factors. Results Factor analyzes suggested a bifactor model of the WHOQOL-AGE, which comprised three specific factors, namely “health,” “environment” and “mastery,” in addition to the general factor (“overall”). Partial scalar invariance (concerning only one item) and scalar invariance were established across gender and education level respectively, generally supporting the measurement invariance of this model. Regression results demonstrated known-groups validity. Health correlates were more predictive of “health” than “environment” and “mastery,” with more basic and instrumental activities of daily living, lower depressive symptomatology and fewer falls positively relating to “health.” Strength of social network and social engagement (social correlates) positively related to “environment” and “mastery” but not “health.” Conclusion The WHOQOL-AGE exhibits a bifactor structure and known-groups validity among the oldest-old Chinese in Singapore. It seems useful to capture different facets of quality of life in the concerned population.